Fundamentals of Entrepreneurship (ENT300) Individual Business Plan Report : Arifah Kitchen Enterprise / Norarifah Md Saad - Md Saad, Norarifah (2020)
Arifah Kitchen Enterprise offers bakery products for customers, providing the variety types of dessert such as cakes, cookies and brownies that the gives high satisfaction of customers. Our target market is customers who like eat dessert at an affordable price. Our product range ranges from RM10- RM200 based on customer orders. Across the state of Kedah especially the Arifah Kitchen Enterprise business has grown steadily success. Sungai Petani is an area where many people get married mainly Muslim Malays, causing demand to rise throughout the year cakes. Our cookies and brownies are also in high demand daily by customers. Arifah Kitchen marketing strategy is to emphasize the quality and price of our products. We offer the affordable price so that everyone can buy it. Thus, we developing marketing strategy that gives attraction to come our shop especially dessert lovers. Arifah Kitchen offers a variety of cakes, cookies and brownies that given nutrition of health, low calories and receive halal certifications. Arifah Kitchen is owned by Norarifah Binti Md Saad. We have 5 employees with experience in the bakery industry. We plan to aggressively build our brand in another state so that everyone can buy our products.